Li Bo Unkempt - Smith, Kidder (punctum books, 2021)
"This is Li Bo. You may also know him as Li Po 李白 (701-62), the great poet of Tang China, master of swoop and soar, wanderer, man of wine, so enamored of the moon that he tried to embrace her reflection in the river, fell from his boat and drowned. Favorite of the Emperor-but only for a while, as such energies cannot be long contained at Court. Li Bo Unkempt presents seventy of his verses, a few letters, some rhapsodies and songs. They dance all through Tang high culture, inhabited by planets, hermit women, swashbucklers, grottos, calligraphers and buffoons, Li Bo's friends, lovers and alter egos. He's too shy, too quick to make introductions, but this volume allows us to hear the poetry's stories, their temperaments, to glimpse their secret economies of exchange. The book also offers background material, brief essays, a kind of Lonely Planet™ guidebook to this extraordinary realm. This way the strange will become familiar, and only then can we appreciate how truly strange it is. The authors and translators regard these poems as magical acts. What is offered, then, in this volume, are multiple ways to realize that magic. The essays are demonstrations, a spell-book, an extension of this non-ordinary knowing. Things too delicate to be said directly. So the book proceeds by analogy, by juxtaposition, latency, innuendo, jump cuts, dialetheia and flirt. All this a way to understand a deeper claim: that Li Bo is an immortal. And what might that be...?"